From samba de roda to rap: musical transits and social markers of differences in contexts of black women resistance in Cachoeira, BA (Orfeu, 2019)
This article presents the contexts surrounding the processes of black women protagonism related to samba de roda and rap in Cachoeira, Recôncavo of Bahia. Marked by their conditions of gender, race/ethnicity and social class, the female interlocutors have their trajectories analyzed since the development of the city from the theoretical contribution of the ethnomusicology studies, feminisms and cultural studies. The methodology is drawn from an ethnographic study of qualitative nature, which focuses on an empirical study based on the author’s dialogue with the interlocutors. It is based on a bibliographical research of the history of Cachoeira, with the aim of tracing the importance of black women for the development of the city, with the samba de roda as the formative of the diasporic cultural identity of the Recôncavo. Through the Critical Analysis of the Discourse of the song lyrics it is possible to perceive the musical genres in question as elements linked to popular culture in different generational aspects and that they can become powers of communicational action through the production of counter-hegemonic discourses.
Keywords: Black women; Music; Feminisms; Popular communication